The Career Choices We Make: Balancing Ambition, Personal Fulfillment, and Life as an Academic Librarian - Pankl, Lis; Jason, Coleman (Association of College & Research Libraries, 2023)
This chapter is for those among us who reach the midpoint of our careers and contemplate taking a higher-level position or doing the opposite and moving to positions that involve less leadership responsibility. We suspect that the ideas we express will apply to many in the profession. However, we acknowledge that gender, race, and identity play a strong role in career paths and opportunities. Yet, who among us has not felt that we could make significant improvements, if only we were in charge? And who among those who are in charge has not once yearned for a release from feeling responsible for the performance of others? Our advice will not apply to everyone; however, we feel that our combined experience is likely to ensure that it is relevant to the majority of professionals in librarianship. We begin by describing our career paths, both of which are quite nonlinear. Our exposition includes reflection on our motivations for the twists and turns we have navigated. We then describe the nature of the work as well as the ways this work has impacted us in the many positions we have had, which collectively span the gamut from library liaison to unit head to department head to dean. Given our diverse experience, we expect that these narratives will resonate with many of you and thereby serve to provide insights relevant to your own situation. Additionally, the contrasting approaches we offer may create opportunities for those who are undecided. After sharing our experiences in academic libraries, we provide practical advice based on the lessons we have learned from our journeys and conversations with many colleagues. Here we present guidance for deciding whether to pursue a position with more or less leadership responsibility. This takes the form of actionable strategies and motivational mindsets. We end with tips for successfully transitioning into a new position and taking full advantage of the opportunities it can provide for growth and fulfillment. Through our explorations and conversations, we conclude that career trajectories depend on highly personal and situational factors for everyone.